Kearifan Mediator Dalam Penyelesaian Perkara Pemutusan Hubungan Kerja (PHK) Secara Mediasi Di Masa Pandemi - Yetniwati, Yetniwati; Muskibah, Muskibah; Harahap, Rahayu Refindowaty (Nagari Law Review, 2024)
The objectives of this research are to: Establish the very concept of risks due to the pandemi in employment relation; establish the wisdom of mediator concept in the settlement of employment termination during pandemi; corroborate the legal principles by means of mediation in the settlement of employment termination during pandemi; to devise strategies for mediator in settling employment termination disputes during pandemi. The completion of this research has been carried out by using juridical normative method, in conjunction with the statutory approach, conceptual approach and case approach. This research discovered that: A wise mediator needs to comprehend the concept of risks arisen from pandemi which consisted of three type of risk: heavy risk, moderate risk, and small risk. Each risk carries different legal implications. The concept of the wisdom of mediator is that there is a third party who is neutral, honest, fair, understands the matter at issue, and is responsible. The mediator must understand the legal principles of mediation which are: the procedure can be done online or offline, the mediator is a neutral party, active, deliberates to reach a consensus, provides recommendation to the party. The recommendations given must be registered to the court. The mediator’s strategy in settling the employment termination disputes is: by preventing the layoffs or termination from occurring; if preventing termination is not successful, recommendations for the termination can be provided. Recommendations for the layoffs or termination can be given after: data collecting procedure related to the case, bargaining process of the parties, formulation of the results of the agreement; submission of the recommendation to the parties.In conclusion: wise mediators should try to avoid layoffs, if layoffs cannot be avoided, they should provide solutions to provide rights and obligations in a balanced manner by taking into account the economic conditions of employers.